PENGARUH RASIO HUTANG, INTENSITAS ASET TETAP, RETURN ON ASSETS (ROA) TERHADAP TARIF PAJAK EFEKTIF PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - SARAGIH , JOANA L.; SIMBOLON, LILIS H.; SITANGGANG, ABDONSIUS (UNIKA Santo Thomas, 2022)
The purpose of this study was to determine the debt ratio, fixed asset intensity, ROA effect on the effective tax rate on food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study was obtained by purposive sampling. With a total sample of 46 companies. The analytical method used is multiple linear regression equation. From the test results, it is known that the value of the coefficient of determination (R Square) is 0.111. This means that the debt ratio, fixed asset intensity and Return On Assets (ROA) together affect the effective tax rate of 11.1%. Based on the results of multiple linear regression analysis, it can be concluded that the debt ratio has a positive and insignificant effect on the effective tax rate on food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019. The intensity of fixed assets has a positive and insignificant effect on the effective tax rate on food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019. ROA has a positive and significant effect on the effective tax rate for food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019.